From the mixed-up files of Mrs. Basil E. Frankweiler - Konigsburg, E. L. (Turtleback Books St. Louis, Mo., 2015)
When Claudia and Jamie plan to run away from home, they decide that the Metropolitan Museum of Art would be a very comfortable place to live. So they settle in and soon find themselves in the middle of a controversy over the authenticity of a new statue